Sepak Bola Mini Sebagai Alternatif Pembelajaran Pjok: Solusi Untuk Sekolah Dengan Keterbatasan Sarana - Rusdiawan, Afif; Wismanadi, Himawan; Widodo, Achmad; Baharuddin, Ayub (Laksana Olahraga, 2025)
Mini soccer socialization is one of the efforts in providing knowledge to PJOK teachers. Mini soccer can be used as a reference for PJOK teachers in providing Physical Education subject matter to students with limited facilities and infrastructure at school. Not only the majority, but all teachers in Lakarsantri District, Surabaya have not understood the knowledge and skills in mini soccer, even though this material is quite important as a modification of soccer learning with schools that have limited facilities and infrastructure at school. The solutions offered in overcoming these problems are (1) Conducting mini soccer socialization, (2) Conducting mini soccer practice, (3) The purpose of this training is to increase the knowledge and skills of PJOK teachers in Lakarsantri District Surabaya in soccer. The targets in this PKM activity are PJOK teachers in Lakarsantri District, Surabaya. The implementation methods carried out are conducting preliminary studies, formulating problem solving, preparing materials, conducting training on the preparation of training programs and evaluating PKM activities. The targeted outputs in this PKM are PKM articles published in national journals, increased understanding and skills of trainers and videos of PKM activities.